Influence of spatial variation in forage availability and predation risk on habitat selection by woodland caribou (Rangifer tarandus caribou) in Ontario - McGreer, Madeleine (University of Guelph, 2014)
Little is currently known about how selection for particular habitats relates to fitness constraints, nor how the strength of selection for specific fitness metrics changes due to variation in habitat availability across broad landscape gradients. I examine site selection by 110 woodland caribou equipped with GPS radio-collars with respect to two fitness-related metrics, forage availability and predation risk, across a broad spatial gradient of forage and risk availability. I found that caribou select habitats that reduce predation risk and improve access to forage. By comparing within-population variation in forage availability and risk prevalence, I found that caribou face a forage-risk trade-off in summer but not winter. Caribou decreased selection strength for forage with forage availability in winter, but not summer. In contrast, caribou in both seasons increased risk avoidance in riskier ranges. These findings suggest that trade-offs other than food versus safety influence caribou habitat use decisions. Forest Ecosystem Science Cooperative Inc. Natural Sciences and Engineering Research Council of Canada Canadian Forest Service Ontario Ministry of Natural Resources